2013
DOI: 10.1194/jlr.m036699
|View full text |Cite
|
Sign up to set email alerts
|

Is the atherosclerotic phenotype of preeclamptic placentas due to altered lipoprotein concentrations and placental lipoprotein receptors? Role of a small-for-gestational-age phenotype

Abstract: Gestational hyperlipidemia is a common factor in pregnancy in which the maternal circulating lipid profile changes from an anabolic to a catabolic state, increasing lipids, especially triglycerides (TGs) and lipoproteins ( 1 ). From the 12th week of gestation, phospholipids, total cholesterol (TC), LDL, HDL, and TGs increase in response to estrogen stimulation and insulin resistance ( 2 ). Thus, during the fi rst two trimesters, it is common to see maternal fat accumulation; however, in the third trimester the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
(33 reference statements)
1
19
0
1
Order By: Relevance
“…A meta-analysis demonstrates that patients with PE have increased levels of TG and TC through pregnancy, as well as lower levels of HDL-C in the third trimester [24]. Other studies do not found any differences of neither TG nor TC levels between PE and uncomplicated pregnancies [25]. Our results illustrated that compared with the control group, the HDP group showed higher TG concentrations and AIP in the second trimester.…”
Section: Discussionsupporting
confidence: 46%
“…A meta-analysis demonstrates that patients with PE have increased levels of TG and TC through pregnancy, as well as lower levels of HDL-C in the third trimester [24]. Other studies do not found any differences of neither TG nor TC levels between PE and uncomplicated pregnancies [25]. Our results illustrated that compared with the control group, the HDP group showed higher TG concentrations and AIP in the second trimester.…”
Section: Discussionsupporting
confidence: 46%
“…However, fetal serum concentrations were significantly lower compared to maternal concentrations, in both groups (21).…”
Section: Introductionmentioning
confidence: 87%
“…The lipoproteins (LDL-C, HDL-C, TC, TG) were previously measured in maternal and fetal serum from the same sample collection (21).…”
Section: Sample Collection and Measurementsmentioning
confidence: 99%
“…Placental protein expression was assessed by immunohistochemistry, as previously described (22), using paraffin-embedded tissue sections (5 µm). Protein expression of ERAP1/ERAP2 using anti-ARTS1/ERAP1 rabbit monoclonal (ab232466; dilution 1:50; Abcam) and anti-LRAP/ERAP2 goat polyclonal (AF3830; 8 µg/ml; R&D Systems) antibodies were used.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%